Use of online approaches to prevent eating disorders: A narrative review (Research, Society and Development, 2021)
Eating disorders are associated with high social and personal costs. Literature has developed prevention studies over the years with positive effects on scholar interventions. As the use of technology has grown in health area, it is necessary to study new forms of remote and far-reaching intervention. The present review aims to present an overview of online interventions for prevention of eating disorders and discuss future paths for the implementing programs in developing countries. From the literature search, nineteen studies that tested online approaches were identified, with most of them based on cognitive behavioral theory or cognitive dissonance. The programs had an impact on reduction of eating disorders risk factors, especially in relation to body dissatisfaction. Despite being non-existent in developing countries, due to the growth of access to technology, investments in online prevention strategies, in countries like Brazil, are promising, since they require less investment and can produce relevant population impacts on problems related to weight, such as eating disorders and obesity.